A critique of the approach to controlling electrostatic risk in semiconductor production and identification of a potential risk from the use of equipotential bonding - Gavin C Rider (AIMS Electronics and Electrical Engineering, 2019)
Equipotential bonding, whereby objects are connected to a common electrical potential (usually ground) to prevent electrostatic discharges during material handling, has been shown to increase the risk of field-induced reticle damage. It is explained how the presence of an electric field can cause electrostatic damage in a reticle without a discharge event taking place. A comparison is drawn between the damage mechanisms that can take place in reticles and in semiconductor devices. The use of equipotential bonding during the manufacture of electrically sensitive semiconductor and micro-electro-mechanical systems is discussed. It is concluded that while equipotential bonding eliminates the risk of ESD during material handling, it simultaneously creates other risks for the devices being manufactured, which has the potential to introduce latent defects. An alternative methodology for dealing with electrostatic risk in semiconductor manufacturing is proposed, which would eliminate the undesirable enhancement of field-induction effects that is a consequence of using equipotential bonding.